The formula for conditional probability is as following:
P(A/B')=P(A∩B') /P(B')
Given P(A ∩ B')=
and P(B')=
.
So, first step is to plug in the given values in the above formula to get the answer. Hence,
P(A/B')=
![((1)/(6))/((7)/(24))](https://img.qammunity.org/2019/formulas/mathematics/college/u8bxnn1or1d7yd0fdv6wei3ptzy1ksn45d.png)
=
(Multiplying both top and bottom by 24).
=
![(4)/(7)](https://img.qammunity.org/2019/formulas/mathematics/high-school/2uwuxz9oawbiwcbjei6rayknvvxrntzp6n.png)
So, P(A/B')=
![(4)/(7)](https://img.qammunity.org/2019/formulas/mathematics/high-school/2uwuxz9oawbiwcbjei6rayknvvxrntzp6n.png)
Hence, the correct choice is B:
![(4)/(7)](https://img.qammunity.org/2019/formulas/mathematics/high-school/2uwuxz9oawbiwcbjei6rayknvvxrntzp6n.png)